Sistema especialista em lógica fuzzy para o controle, gerenciamento e manutenção da qualidade em processo de aeração de grãos - Bilobrovec, Marcelo (2005)
This work presents a specialist system for automatic control and management of the process of aeration of grains and to maintain the quality them, using the Fuzzy Logic. It makes possible the aeration of the maize grains in rational way in vertical storage system taking care of the necessities for the storage as for the conservation. A prototype has been developed that allows the assay and the verification of the necessity of aeration of certain mass of maize grains, through the analysis of the conditions of ambient temperature, the mass of grains temperature and the relative humidity of air. The implementation of the actions and control uses the Fuzzy Logic, making possible the capture of the knowledge of specialists. In the same way allows the comparation of the diversity of opinions between the pairs, the excellent moment of the intervention. The system uses sensors to measure humidity and temperature, which are input variables of the process. The interaction between the acquired values by the rules of inference of the specialist system in Fuzzy Logic, creates the actions of aeration control. The developed system able indicates the aeration in compliance with the Rational Conduction of Aeration Diagram developed by the Technical Cereals and Fodder Plants Institute (ITCF), situated in France. In this way, capable to operate automatically the control of the aeration system.